Chitosan derived layered porous carbon and its performance on gallium adsorption. Issue 6 (13th March 2023) - Cui, Junshuo; Cong, Xiaoshan; Li, Xinzhu; Chen, Xia; Wang, Yuejiao; Gao, Jing; Xiong, Ying
Abstract: BACKGROUND: Gallium (Ga) is widely used in the preparation of low‐melting alloys and is also mainly used in electronics. However, Ga is a rare‐scattered element that has no independent ore deposits. Fortunately, adsorbents with high specific surface area have shown great potential for the recovery and enrichment of Ga from mineral industry wastes or recycled electronics. Consequently, porous carbons with hierarchical layered structures were prepared as adsorbent for the recovery of Ga. Besides the routine hydrothermal and carbonizing treatments, chitosan (CS) derivatives were further activated by potassium hydroxide, zinc chloride, and ferric trichloride to improve their respective specific surface areas. RESULTS: Nitrogen adsorption analysis showed that the porous carbon activated by KOH at 800 °C (CS‐800) had the highest specific surface area (2997 m 2 g −1 ). The maximum adsorption capacity for Ga(III) was 129.83 mg g −1, which is better than that of other well‐known carbon based adsorbents. CS‐800 also exhibited good selectivity for Ga(III) among various competitive ions, such as Zn(II), Cu(II), Ge(IV), and Al(III). In addition, the adsorbent showed good reusability; the recovery percentage of Ga(III) remained above 90% after six adsorption‐elution experiments. CONCLUSION: KOH is an ideal activating agent to increase the surface area of porous carbon and 800 °C is its optimal temperature. This agent can provide sufficient active surface sites for metal ions adsorption. This work provides a strategy for the regulation of CS derived porous carbon and is expected to play a key role in real applications for the recovery of Ga. © 2023 Society of Chemical Industry (SCI).